International variation in programmes for assessment of children's neurodevelopment in the community: Understanding disparate approaches to evaluation of motor, social, emotional, behavioural and cognitive function. Issue 8 (December 2018) - Wilson, Philip; Wood, Rachael; Lykke, Kirsten; Hauskov Graungaard, Anette; Ertmann, Ruth Kirk; Andersen, Merethe Kirstine; Haavet, Ole Rikard; Lagerløv, Per; Abildsnes, Eirik; Dahli, Mina P.; Mäkelä, Marjukka; Varinen, Aleksi; et al.
Background: Few areas of medicine demonstrate such international divergence as child development screening and surveillance. Many countries have nationally mandated surveillance policies, but the content of programmes and mechanisms for delivery vary enormously. The cost of programmes is substantial but no economic evaluations have been carried out. We have critically examined the history, underlying philosophy, content and delivery of programmes for child development assessment in five countries with comprehensive publicly funded health services (Denmark, Finland, Norway, Scotland and Sweden). The specific focus of this article is on motor, social, emotional, behavioural and global cognitive functioning including language. Findings: Variations in developmental surveillance programmes are substantially explained by historical factors and gradual evolution although Scotland has undergone radical changes in approach. No elements of universal developmental assessment programmes meet World Health Organization screening criteria, although some assessments are configured as screening activities. The roles of doctors and nurses vary greatly by country as do the timing, content and likely costs of programmes. Inter-professional communication presents challenges to all the studied health services. No programme has evidence for improved health outcomes or cost effectiveness. Conclusions: Developmental surveillance programmes vary greatly and their structure appears to be driven by historical factors as much as by evidence. Consensus should be reached about which surveillance activities constitute screening, and the predictive validity of these components needs to be established and judged against World Health Organization screening criteria. Costs and consequences of specific programmes should be assessed, and the issue of inter-professional communication about children at remediable developmental risk should be prioritised.